Enhancement of Green Leaf Yield in Tea [Camelia sinensis (L.) O Kuntze] as a Function of Pigments by Foliar Application of Triacontanol - Maity, Utpal; Dutta, Puspendu; Laya, Bijoy; Chaudhuri, Kajal Mog (International Journal of Bio-resource and Stress Management, 2019)
Tricontanol is a natural plant growth regulator that possesses growth promoting activity and it is also able to increase leaf pigment and thereby improving yield of various crops. Plant pigments particularly leaf chlorophyll contents have widely been appraised as the most significant indicator of photosynthesis. Tea is one of the most important leverage in the world but its productivity needs to be increased to meet up the ever increasing demand of tea in coming years. Thus in the present experiment the effect of foliar application of triacontanol on green leaf yield as a function of chlorophyll and carotenoids contents of field grown mature tea was evaluated. Total six numbers of triacontanol (0.1% EW) treatments @ 0.3, 0.4, 0.5, 0.6, 0.8 and 1.0 ml l-1 of water, besides two control treatments, viz. untreated control and water spray were used. Total chlorophyll content in the various leaves viz. bud, 1st, 2nd and matured leaves were estimated during each plucking which was continued up to fourth round. It was observed that triacontanol exerted a markedly positive effect on leaf pigment contents and green leaf production of tea. The results further indicated that the total chlorophyll contents of matured leaves were positively associated with green leaf yield at fourth round of plucking. The application of triacontanol i.e. @ 0.5 ml l-1 at three weeks interval may be recommended for tea since this treatment was found to produce more green leaves as compared to others irrespective of plucking rounds.